2023
DOI: 10.1002/jemt.24291
|View full text |Cite
|
Sign up to set email alerts
|

Unique structures and material properties of the skin in different body regions of three species of fish

Abstract: Benefitting from its unique helically arranged fiber structures, fish skin is a superior biological protective tissue. Reported here is a study of the microscopic morphological characteristics and mechanical properties of the skin of three species of fish, that is, Taihu white fish (Erythroculter ilishaeformis), grouper (Cichlasoma managuense), and yellowfin seabream (Ditrema temminckii Bleeker), revealing the special protective mechanisms of fish skin. Experiments involving scanning electron microscopy show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The authors further revealed that s. compactum plays an essential role in fish movement and protective functions and significantly improves the biomechanical properties of fish skin. Furthermore, Zheng et al studied the mechanical protective behaviors of the fish skin of three different fish species living in different water areas, namely Taihu white fish ( Erythroculter ilishaeformis , from freshwater), grouper ( Cichlasoma managuense , which live in both freshwater and seawater), and yellowfin seabream ( Ditrema temminckii Bleeker , from the ocean) [ 13 ]. They found that for the three fish species, s. compactum plays a vital role in the protective behaviors of the fish skin.…”
Section: Introductionmentioning
confidence: 99%
“…The authors further revealed that s. compactum plays an essential role in fish movement and protective functions and significantly improves the biomechanical properties of fish skin. Furthermore, Zheng et al studied the mechanical protective behaviors of the fish skin of three different fish species living in different water areas, namely Taihu white fish ( Erythroculter ilishaeformis , from freshwater), grouper ( Cichlasoma managuense , which live in both freshwater and seawater), and yellowfin seabream ( Ditrema temminckii Bleeker , from the ocean) [ 13 ]. They found that for the three fish species, s. compactum plays a vital role in the protective behaviors of the fish skin.…”
Section: Introductionmentioning
confidence: 99%